2005
DOI: 10.1152/ajpcell.00569.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antimitogenic effect of green tea (−)-epigallocatechin gallate on 3T3-L1 preadipocytes depends on the ERK and Cdk2 pathways

Abstract: Green tea catechins, especially (-)-epigallocatechin gallate (EGCG), have been proposed as a chemopreventative for obesity, diabetes, cancer, and cardiovascular diseases. However, relatively little is known about the mechanism of the action of EGCG on fat cell function. This study was designed to investigate the pathways of EGCG's modulation of the mitogenesis of 3T3-L1 preadipocytes. Preadipocyte proliferation as indicated by an increased number of cells and greater incorporation of bromodeoxyuridine (BrdU) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
129
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 46 publications
9
129
1
3
Order By: Relevance
“…Several other evidences have suggested that EGCG inhibited MAPKs activity to regulate diverse cellular responses in different cell types. EGCG suppressed phosphorylation of ERK 1/2 in the 3-L1 preadipocytes (Hung et al, 2005), and that of ERK and JNK in human gastric cancer AGS cells . EGCG inhibited JNK activity in bFGF-stimulated VSMC (Hwang et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Several other evidences have suggested that EGCG inhibited MAPKs activity to regulate diverse cellular responses in different cell types. EGCG suppressed phosphorylation of ERK 1/2 in the 3-L1 preadipocytes (Hung et al, 2005), and that of ERK and JNK in human gastric cancer AGS cells . EGCG inhibited JNK activity in bFGF-stimulated VSMC (Hwang et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…185,186 In vitro data suggest that the anti-obesity effects of green tea could in part be mediated through the inhibition of adipocyte division and maturation. [187][188][189] There is also evidence that green tea could reduce glucose and fat absorption by inhibiting GI enzymes involved in nutrient digestion. 190,191 Juhel et al 192 reported that in vitro the green tea extract AR25 (Exolise ® ; standardized at 25% catechins) effectively inhibited gastric and pancreatic lipase activities.…”
Section: Green Teamentioning
confidence: 99%
“…Digestive enzyme inhibition in the management of obesity 73,203 Green tea catechins 5-30 μM inhibit adipocytes differentiation inhibit gastric and pancreatic lipase inhibit α-amylase and α-glucosidase [187][188][189]191,192 Cyclocarya paliurus 5 μg/mL 9.1 μg/mL inhibits α-glucosidase inhibits pancreatic lipase 180,181 Salacia reticulata polyphenol extracts salacinol and kotalanol iC 50 Once bound to these surfaces, colipase facilitates the interaction between pancreatic lipase and the surface of emulsified lipid droplets. 20 Although HPLRP1 and -2 share a high degree of structural homology and sequence with HPL, 21 their role in lipid digestion has not been fully clarified.…”
mentioning
confidence: 99%
“…It has been reported that adzuki bean extract contains some familiar physiologically active substances, such as catechin and saponin [15,16,17,18]. Catechin and epigallocatechin gallate (EGCG) are also reported to inhibit the differentiation of 3T3-L1 adipocytes [19,20]. The next step is to identify the active ingredients within the extract.…”
Section: Discussionmentioning
confidence: 99%